It takes a family : conservatism and the common good - Santorum, Rick, 1958-; Intercollegiate Studies Institute (Wilmington, Del. : ISI Books, 2005)
In his first book, Senator Santorum articulates the humane vision that he believes must inform an effective and just public policy. At the heart of genuine conservatism lies an appreciation for the civic bonds that unite a community. Santorum demonstrates how such an approach to political, social, and economic problems offers the most promise for those on the margin of life: the poor, the vulnerable, and minorities who have often been excluded from opportunity in America. Building on Robert Putnam's discussion of "social capital, " the habits of association and trust that are the preconditions of any decent society, Santorum assesses how well Americans have cared for the "fabric" of society. He explores various dimensions of social and cultural connection that are the foundation of the common good. And he presents policy proposals for the renewal of American society at all levels.--From publisher description.
It takes a family -- Social capital and the ties that bind -- The roots of prosperity -- Moral ecology -- Culture matters -- Educational excellence.
Includes bibliographical references (p. [429]-436) and index.
Keywords: Families -- United States; Politics and culture -- United States; Christian conservatism -- United States; United States -- Politics and government -- 2001-; United States -- Economic policy -- 2001-